CHARACTERISTICS AND VISITING MOTIVES ANALYSIS OF DOMESTIC TOURISTS TO TOURISM DESTINATIONS OF PROVINCE LAMPUNG - M. Ariza Eka Yusendra; Yusminar Wahyuningsih (Proceeding International Conference on Information Technology and Business, 2016)
Lampung province also one of provinces that put the tourism sector as a development priority. It can be seen from the development priorities of Lampung Province in 2015-2020, one of them is